2021
DOI: 10.1080/03004430.2021.1885390
|View full text |Cite
|
Sign up to set email alerts
|

Fidelity of implementation of activity-based intervention in daycare

Abstract: Despite the recognized effectiveness of naturalistic intervention practices, including activity-based intervention (ABI), challenges remain regarding their implementation. Assessing implementation fidelity can help understand factors that may influence their implementation. This study aims to document the evolution of ABI implementation fidelity (Adherence, Dosage, Quality and Participant responsiveness) in daycare settings following professional development. The participants are four educators. The current st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 40 publications
(40 reference statements)
0
1
0
Order By: Relevance
“… 33 The measurement and reporting of implementation fidelity can provide information about whether implementation strategies are sufficient and if additional or different strategies are needed. 34 A recent review found that the level of implementation of ECEC-specific policies and practices were low and implementation strategies were insufficient to change these outcomes. 12 Measuring implementation fidelity, therefore, is necessary for understanding the success of ECEC-specific physical activity interventions.…”
Section: Introductionmentioning
confidence: 99%
“… 33 The measurement and reporting of implementation fidelity can provide information about whether implementation strategies are sufficient and if additional or different strategies are needed. 34 A recent review found that the level of implementation of ECEC-specific policies and practices were low and implementation strategies were insufficient to change these outcomes. 12 Measuring implementation fidelity, therefore, is necessary for understanding the success of ECEC-specific physical activity interventions.…”
Section: Introductionmentioning
confidence: 99%